A hemi‐spleen injection model of liver metastasis for prostate cancer. Issue 14 (6th August 2020) - Simons, Brian W.; Dalrymple, Susan; Rosen, Marc; Zheng, Lei; Brennen, W. Nathaniel
Abstract: Background: Liver metastasis is not uncommon in men with metastatic castration‐resistant prostate cancer (mCRPC), estimated at ~20% to 60% of advanced late‐stage patients. Liver and other visceral metastases are associated with worse overall survival. Recent evidence suggests the frequency of visceral metastases may be increasing for reasons that are unclear but may be related to selective pressures induced by modern therapies, including second‐generation antiandrogen receptor signaling inhibitors such as enzalutamide and abiraterone. Consequently, robust models to study the pathobiology of prostate cancer liver metastases and their response to therapy are urgently needed. Methods: Hemi‐spleen injection of human (LN95, PC3, VCaP, and MDA‐PCa‐2b) or syngeneic (Myc‐CaP) prostate cancer cells (1 × 10 6 ) was performed to seed liver metastases via the splenic vessels. Plasma levels of prostate‐specific antigen (PSA) were monitored longitudinally in human androgen receptor‐positive (AR+) models. Immunohistochemical staining of AR and HoxB13 was performed to document the prostatic origin of hepatic lesions. Results: LN95, PC3, and Myc‐CaP produced distinct liver micrometastases that progressed to macrometastases by ~2 to 4 weeks postinoculation, while inoculation of MDA‐PCa‐2b and VCaP only produced occasional micrometastases and seeding of individual cells adjacent to blood vessels, respectively, at the time points analyzed. All lesions are characterized by positive staining for nuclear AR and/or the prostate‐specific differentiation marker HoxB13 depending on the model. Circulating PSA levels are strongly correlated with overall tumor burden in mice seeded with LN95. Histologic micrometastases and low levels of circulating PSA are detected in mice seeded with MDA‐PCa‐2b at ~60 days postinoculation, but no circulating PSA was detected in animals inoculated with VCaP up to ~75 days despite the presence of rare AR+ cells in the liver. Conclusion: The studies reported herein establish intrasplenic injection as a robust model of mCRPC liver metastasis. In addition, circulating PSA was validated as a noninvasive biomarker to longitudinally monitor overall tumor burden when using PSA+ models. Therefore, this model can be used to interrogate the pathophysiology of prostate cancer liver metastases, the microenvironmental factors permissive to such growth, immunologic variables, and the response of hepatic lesions to therapy.